2015
DOI: 10.4314/ahs.v15i2.44
|View full text |Cite
|
Sign up to set email alerts
|

Educational audit on drug dose calculation learning in a Tanzanian school of nursing

Abstract: Background: Patient safety is a key concern for nurses; ability to calculate drug doses correctly is an essential skill to prevent and reduce medication errors. Literature suggests that nurses' drug calculation skills should be monitored. Objective: The aim of the study was to conduct an educational audit on drug dose calculation learning in a Tanzanian school of nursing. Specific objectives were to assess learning from targeted teaching, to identify problem areas in performance and to identify ways in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
7
0
6
Order By: Relevance
“…Without specific disease focus (27 questions; 6 papers). Six papers (14%) with 27 medication-related knowledge questions did not have a specific disease focus (grouped under 'other' in Table 2) [16,18,[75][76][77][78]. Questions were more general including self-medication, topical medications (antipain and antibiotics), dose calculation and prescribing errors.…”
Section: Non-communicable Diseases (38 Questions; 8 Papers)mentioning
confidence: 99%
“…Without specific disease focus (27 questions; 6 papers). Six papers (14%) with 27 medication-related knowledge questions did not have a specific disease focus (grouped under 'other' in Table 2) [16,18,[75][76][77][78]. Questions were more general including self-medication, topical medications (antipain and antibiotics), dose calculation and prescribing errors.…”
Section: Non-communicable Diseases (38 Questions; 8 Papers)mentioning
confidence: 99%
“…Recent literature defines wrong drug dosage error as an inconsistency between the dose administered and the dose prescribed (Wright, 2010). Medication safety is a major concern and a global issue related to quality and safety of patient care (Savage, 2015;Shamsuddin & Shafie, 2012). A study conducted on economic measurement of medical errors in hospital setting reported that 44,000 to 98,000 medical errors cause serious adverse event every year in the United States (David, Gunnarsson, Waters, Horblyuk, & Kaplan, 2013).…”
Section: Drug Dosage Calculation Errorsmentioning
confidence: 99%
“…Mathematical and dosage calculation proficiency is very important skill for nurses in order to ensure patient safety and delivery of quality care (Athanasakis, 2012;Cheragi, et al, 2013;Fleming, et al, 2014;Savage, 2015;Sulosaari et al, 2015;Wright, 2004). Recent review of literature reports that presently medication errors are focused in healthcare in the light of official reports in United States and the United Kingdom that highlighted the significant of medication errors occurring in hospitals.…”
Section: Drug Dosage Calculation Errorsmentioning
confidence: 99%
“…1 One of the main tasks of nurses and nursing students is the correct drug dose calculation. 2,3 Therefore, students must have the necessary knowledge and ability in the fields of pharmacology and mathematical computation. 4 One of the most important causes of medication mistakes is incorrect drug dose calculation and low pharmacological knowledge, 5 which can lead to prolonged hospitalization and cost increases and in some cases may lead to irreparable damage and even the death of patients.…”
Section: Introductionmentioning
confidence: 99%